Authenticity Analysis of Cold-Pressed Orange Essential Oils by GC/MS on Polymethoxyflavone Components - Kai-Min Yang; Chih-Wei Chen; Min-Hung Chen; Hsin-Chun Chen; Li-Yun Lin (Agriculture, 2023)
Citrus essential oil combines numerous components with many qualities and control issues. For example, how to monitor volatile components and nonvolatile substances simultaneously is a major problem. Therefore, the objective of this study was to develop a Gas chromatography/mass spectrometry (GC/MS) method for the compositional study of total constituents in cold-pressed essential oils from major orange species. A polysiloxane GC column (DB-1, nonpolar, low-bleeding) was used in this study; its fingerprint includes terpenoids (Section 1), long-chain hydrocarbons (Section 2), phytosterols, and polymethoxyflavones (Section 3). These markers are more effective in detecting adulteration of essential oil products than volatile components, and more effective than quantitative PMF by 5α-Cholestane for establishing authenticity. The study aims to use the analysis procedure as a routine quality control test for authenticity evaluation in cold-pressed orange essential oils (CP-OrEO).